CHRONIC HEPATITIS OR «DISGUISE» PAROXYSMAL NOCTURAL HEMOGLOBINURIA? - D. A. Dolgopolova; E. E. Zinina; Yu. A. Sedlova (Klinicist)
Objective is description of a case of diagnostics of a paroxysmal nocturnal haemoglobinuria. Subjects and methods. The male patient of 50 years asked for medical care with complaints to emergence of yellowness a skin, urine darkening, not expressed general weakness. To the patient examination was conducted: clinical and biochemical blood tests, urine, miyelogramm, definition of an index of sphericity of erythrocytes, definition of free hemoglobin of plasma of blood, urine, gemosiderinuriya, flow citometry, immunological markers of rheumatic diseases, tool inspection, etc. Results. On the basis of complaints, a clinical picture of a disease, data of objective and tool inspections the final diagnosis is made: a paroxysmal nocturnal haemoglobinuria, a classical haemolytic form (on the International classification of diseases of the 10th revision – B 59.5). The comorbid diagnoses: anemia of heavy degree; transfusion dependence; thrombosis of a subclavial vein on the right (11.2011); cholelithiasis; chronic calculous cholecystitis in remission; chronic hepatitis of the mixed genesis (alcoholic, metabolic), moderate degree of activity. By the main diagnostic method which allowed to verify the diagnosis became flow citometry. According to an flow citometry erythrocytes I Tip (normal expression of CD59) – 87,0 %, II Type (partial deficiency of CD59) – 0,3 %, III Type (full deficiency of CD59) – 12,7 %; monocytes with deficiency of FLAER/CD14 – 93,3 %; granulocytes with deficiency of FLAER/CD24 – 97,7 %. Flow citometry was revealed by availability of APG-clone among erythrocytes, granulocytes and monocytes. Judging by the huge size of a clone (on granulocytes 97,7 %), it is possible to draw a conclusion that the patient was in the highest zone of risk of APG of crises. Conclusion. Practical interest of this supervision is caused by a rarity of this hematologic disease, the analysis of modern opportunities of diagnostics and complexity of a choice of tactics of treatment. The medicinal therapy which allowed to reduce quantity of haemolytic crises – application of a preparation eculizumab is picked up.